Education : project on institution building : administrative arrangements for implementing devolution - Munsoor, M. M.; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2001)
With reference to Sri Lanka.
Keywords: Education -- Aims and objectives -- Sri Lanka; Education and state -- Sri Lanka